O polimorfismo I/D do gene ECA e nefropatia diabética: evidências baseadas em meta-análises - Silveira, Luciana Carvalho (2018)
Diabetic Nephropathy (DN) is a microvascular renal complication of Diabetes Mellitus (DM), characterized by increased albuminuria and progressive loss of renal function. A cumulative incidence of ND in the last 10 years was observed in 40%, mainly in patients with type 2 diabetes mellitus (T2DM), being an important cause of morbidity and mortality among these individuals. The Insertion / Deletion (I/D) polymorphism in the ACE gene could influence the predisposition to DN by vascular modulation in the kidney, through a direct effect on the cellular hypertrophy, influencing the proliferation and the rupture of the extracellular matrix. Many studies about this subject are discordant, a fact that increases the need for joint analysis so that safe conclusions can be generated. The aim of this study was to investigate the association between ACE gene I/D polymorphism and the development of DN in patients with T2DM. Through a standardized research protocol, the bibliographic search was performed in the PubMed and Cochrane Library electronic databases of 1995-2017, selecting case-control observational studies using the terms "polymorphism" AND " ACE gene" AND “diabetic nephropathy ". We included 33 studies in qualitative synthesis and 30 studies for meta- analysis, with 9.077 participants with T2DM genotyped, 4.774 (52, 6%) individuals with DN and 4.303 (47. 4%) individuals without DN. Evaluated separately, the genotypes for the case group, we have I/I (23, 5%), I/D (46, 4%) and D/D (30, 6%). The genotypes for the control group, I/I (28, 6%), I/D (46.19%) and D/D (25%). The highest prevalence observed was of the I/D genotype in both groups. In the allele frequencies calculated by the Hardy-Weinberg Test, the mutant D allele presents with 54% in the case group and 48% in the control group. The wild-type I allele was present in 46% in the case group and 52% in the control group. The present meta-analysis concludes the I/D polymorphism of the ACE gene studied through the I/D and D/D genotypes is not associated with the risk of developing DN in individuals with T2DM, but the presence of the D allele has significant significance in the risk of developing the disease, as well as the protective role of the I allele.